Sidewalk thermal comfort in street canyon and role of pavements under perpendicular sun rays during summer - D. Jareemit; M. Srivanit (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The reflection of solar radiation by pavements is crucial for managing urban heat, enhancing thermal comfort, and supporting sustainable development. Albedo pavements are a key component of modern urban planning. Despite extensive studies on the influence of pavement reflectivity on heat stress in street canyons, there is still a lack of exploration regarding its impact on pedestrian comfort in Thailand during the peak summer months. This study examines thirteen design scenarios and simulations utilizing a microclimate model, with a specific focus on the combined albedos of road surfaces, sidewalks, and plants in a deep street canyon within a residential townhouse project located in Bangkok.METHODS: The utilization of a microclimate simulation model enabled the calculation of climatic conditions within an east-west-oriented street canyon on April 26, which represents a typical summer day in Thailand. By utilizing the simulated microclimatic parameters, hourly physiologically equivalent temperature values were derived to assess human thermal comfort. This analysis helped identify the threshold for comfortable summer conditions in Thailand. Field data validation showed acceptable errors (R² = 0.91, normalized mean square error = 0.17).FINDINGS: For an east-west-oriented deep street canyon with direct overhead sunlight in summer, low-albedo materials for road and sidewalk surfaces are recommended to enhance thermal comfort. The implementation of these albedo strategies has the potential to enhance thermal comfort by 0.34-0.38 percent and alter the threshold values of the Physiologically Equivalent Temperature Index for thermal sensation, transitioning from hot to cold environments. While the percentage increase may seem small, it signifies a substantial advancement in improving thermal comfort for people in urban settings. This finding carries significant importance in densely populated areas with limited natural shade, where even slight improvements in thermal comfort can have a positive effect on public health and well-being.CONCLUSION: Albedo reduction alone may not significantly enhance outdoor comfort within the street canyons. Urban planners and designers should consider integrating additional strategies such as tree planting, Sidewalks facing different directions, exposed to sunlight, instead of pedestrian arcades and overhead shading structures. The thermal environments and comfort of sunlit north-facing sidewalks in an east-west-oriented deep street canyon during the summer, when the sun's path shifts northward, are greatly influenced by the solar tilt and azimuth angles. It is crucial to highlight the substantial impact of these angles.